Biological mechanisms of natural cytoprotection - a promising trend in the development of new medicines aimed at prevention and treatment of preeclampsia - M. V. Pokrovsky; V. V. Gureev; E. G. Stupakova; O. E. Antsiferova; T. I. Lokteva; L. A. Zhilinkova (Регуляторные исследования и экспертиза лекарственных средств, 2018)
Preeclampsia is a frequent and dangerous disease in pregnancy which has shown no decrease in incidence. The article describes preeclampsia pathogenesis as reported in recent studies. A promising trend in the development of new medicines aimed at prevention and treatment of preeclampsia is the activation of biological processes of cytoprotection which arise during ischemic preconditioning. The article cites experimental and clinical data that help to justify the good potential of this area of research.